Objectification of Women in Mobile Legends: A Study Under Ministerial Regulation No. 2/2024 - Sukadi, Imam; Rakhmah, Kamiliya Noer; Aminullah, Irma (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
Women's objectivity is still rampant through sensual representation in character games online. This certainly requires the right solution so that it can be minimized, as a state of law Indonesia has tried to overcome these problems by establishing Regulation of the Minister of Communication and Information Technology Number 2 of 2024 concerning Game Classification. The purpose of this study is to examine the suitability of the Mobile Legends: Bang Bang game with the Regulation of the Minister of Communication and Information Number 2 of 2024 concerning game classification. The research method used is normative juridical by taking a legal approach and a case approach.  The results of this study show that the Mobile Legends: Bang Bang game does not comply with the classification and requirements set out in the Regulation of the Minister of Communication and Information Number 2 of 2024 concerning game classification because the heroes in the game are described as resembling women with an impression of sensuality as depicted in the heroes Layla, Kadita, Odette, Miya, and Fanny. The phenomenon of sensual objectivity in the female hero character of the Mobile Legends: Bang Bang game affects the reality of social life and the relationship between men and women. The recommendations that can be given are (1) the government through the Ministry of Information and Telecommunications must immediately block the Mobile Legends: Bang Bang game because it shows women's sensuality, (2) the government must immediately carry out strict supervision of the phenomenon of games that show women's sensuality. It needs comparative studies analyzing similar issues across different games and jurisdictions to provide a more comprehensive understanding of global trends and potential solutions. These efforts would contribute to more holistic strategies for addressing gender objectification in digital media.